The role of angiotensin I converting enzyme insertion/deletion polymorphism in the severity and outcomes of COVID-19 patients - Rezaei, Mitra; Mohammadpour, Hadiseh; Eftekhari, Mahya; Pourabdollah, Mihan; Nasr Azadani, Farinaz; Tabarsi, Payam; Marjani, Majid; Ziai, Seyed Ali (Frontiers in Genetics, 2022)
The pandemic of coronavirus disease in 2019 has led to a global crisis. COVID-19 shows distinct clinical manifestations of the severity of symptoms. Numerous patients with no associated risk factors demonstrate acute respiratory distress syndrome (ARDS). The role of genetic factors in determining the severity and outcome of the disease remains unresolved. The purpose of this study was to see if Angiotensin I Converting Enzyme (ACE) insertion/deletion (I/D) polymorphism influences the severity of patients' symptoms. 120 COVID-19 patients admitted to Masih Daneshvari Hospital in Tehran with their consent to participate entered the study. Based on the WHO classification, patients were divided into moderate and severe groups, which were primarily affected by O2 saturation levels. The effects of the patients' ACE insertion/ deletion polymorphism, background disease, Angiotensin receptor blocker (ARB) drug consumption, and demographic parameters on the severity risk were calculated statistically. The ACE D allele was associated with an increased risk of disease severity (OR = 6.766, p = 0.012), but had no effect on mortality.